O jovem e o ficar à luz da teoria Bourdiana - Nogueira, Natália Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Nowadays stands out the way in which people experience their love relationships, including the hook up, which has as main characteristics the short time, the lack of commitment, and the engagement with several partners. In this context, this research aimed to investigate the hook up, through the habitus and the trajectory of life of young people. The methodology is qualitative whose main technique for data collection was semi-structured interview. Therefore, young people were interviewed from 18 and 30 years old, both genders, graduate of the pedagogy course at a public university in the state of São Paulo. Furthermore, the theoretical reference of Pierre Bourdieu gave birth to interpretation of data obtained. About the results of the research, these reveal some regularity in the trajectory of young people when the subject is sexuality and sexual education, because young people admitted receiving specific instructions on these subjects in the socialization agents (family and school). In the framework hook up, the results show that for young people this is a short relationship, without ties and commitment, it has been represented since the act of kissing to a pre-dating status. In conclusion, it is found that it isn't part of the family and school habitus to discuss about sexuality and sexual education, because it is a difficult and costly process for those involved. About hook up, the young people interviewed describe that it is part of their habitus the experience of this relationship and the people in your social life

Na atualidade destaca-se o modo com que as pessoas vivenciam suas relações amorosas, entre elas o ficar, que é caracterizado pela curta duração de tempo, a falta de compromisso, e o envolvimento com vários parceiros. Nesse contexto, esta pesquisa teve por objetivo investigar o ficar por meio do habitus e da trajetória de vida dos jovens. A metodologia é qualitativa, cuja técnica principal de coleta de dados foi a entrevista semiestruturada; para tanto, foram entrevistados jovens entre 18 e 30 anos de idade, de ambos os gêneros, graduandos do curso de Pedagogia de uma Universidade Pública no interior do Estado de São Paulo. Ademais, o referencial teórico de Pierre Bourdieu deu luz à interpretação dos dados obtidos. Quanto aos resultados da pesquisa, esses revelam certa regularidade na trajetória dos jovens quando o assunto abordado é sexualidade e educação sexual, pois os mesmos admitiram receber instruções pontuais sobre esses assuntos nas agências de socialização: família e escola. No âmbito do ficar, os resultados mostram que para os jovens esta é uma relação de curto prazo, sem vínculos e compromisso, sendo representado desde o ato de beijar até um estado pré-namoro. Como conclusão, verifica-se que não faz parte do habitus da família e da escola discorrer sobre a sexualidade e a educação sexual, pois ainda é um processo difícil e custoso para os agentes envolvidos. Sobre o ficar, os jovens entrevistados descrevem que faz parte do seu habitus, a vivência dessa relação e a das pessoas que integram seu convívio social
Keywords: Bourdieu, Pierre 1930-2002; Educação sexual; Jovens - Comportamento sexual; Adolescência; Amor na adolescência; Young adults Sexual behavior